Dias de escuela - Hennessy, B. G. (Barbara G.); Pearson, Tracey Campbell (New York : Scholastic, 1995)
Text and illustrations describe the familiar faces and objects of a day at school.
Keywords: Schools -- Juvenile fiction; Fiction